Increased Lateral Tibial Slope Is a Risk Factor for Pediatric Anterior Cruciate Ligament Injury: An MRI-Based Case-Control Study of 152 Patients. (July 2015) - Dare, David M.; Fabricant, Peter D.; McCarthy, Moira M.; Rebolledo, Brian J.; Green, Daniel W.; Cordasco, Frank A.; Jones, Kristofer J.
Background: Increased posterior tibial slope is associated with increased risk of anterior cruciate ligament (ACL) injury in adults. A similar association has not been rigorously examined in children and adolescents. Purpose: To determine whether alterations in posterior tibial slope are associated with ACL tears in pediatric and adolescent patients and to quantify changes in tibial slope by age. Study Design: Case-control study; Level of evidence, 3. Methods: Magnetic resonance imaging (MRI) studies of the knee were reviewed by 3 raters blinded to each other in a 1:1 sample of cases and age- and sex-matched controls. A total of 76 skeletally immature ACL-injured knees were compared with 76 knees without ACL injury; the mean age of the study population was 14.8 ± 1.3 years. The posterior slope of the articular surface of the medial tibial plateau and lateral tibial plateau was measured by use of a method similar to that used in previous studies in adult populations. The current study technique differed in that the slope was measured on the cartilage surface, not the subchondral bone. Comparisons between knees were made with t tests, and Spearman correlation analysis was used to assess changes in tibial slope with advancing age. Results: Increased slope of the lateral tibial plateau (LTS) was significantly increased in ACL-injured patients compared with controls (5.7° ± 2.4° vs 3.4° ± 1.7°; P < .001). There was no statistically significant difference in the slope of the medial tibial plateau (MTS) in the ACL-injured and control knees (5.4° ± 2.2° vs 5.1° ± 2.3°; P = .42). There was no difference in LTS between male and female patients (4.46° vs 4.58°; P = .75). Receiver operating characteristic (ROC) analysis of the LTS revealed that a posterior tibial slope cutoff of >4° resulted in a sensitivity of 76% and a specificity of 75% for predicting ACL tears in this cohort. Spearman correlation analysis revealed that MTS and LTS decreased, or flattened, by 0.31° ( P = .028, correlation coefficient r = −0.18) and 0.37° ( P = .009, correlation coefficient r = −0.21) per year, respectively, as adolescents age. Conclusion: The LTS was significantly associated with an increased risk of ACL injury in pediatric and adolescent patients. The MTS was not associated with risk of injury. Posterior slope was found to decrease, or flatten, with age. A cutoff of >4° for the posterior slope of the lateral compartment is 76% sensitive and 75% specific for predicting ACL injury in this cohort. The LTS did not influence the incidence of ACL injury differently between sexes.